Simulation of dilute acid hydrolysis of wood sawdust for xylose production using aspen plus - N H, Ibrahim; W H, W Ibrahim; Mimi Sakinah, A.M.; N Harun, Harun; Mohamad Rizza, Harun (AENSI Publishing, 2017)
Dilute acid hydrolysis is one of the most effective and inexpensive pretreatment methods for lignocellulosic biomass. Generally in hydrolysis process, monomeric sugars and soluble sugar oligomers (xylose and glucose) from the cell wall matrix are released into the hydrolysate. The aim of this study is to develop and simulate process model including heating, hydrolysis, neutralization, separation and cooling process for xylose production using Aspen Plus simulator. Based on experimental study for xylose production, a flowsheet has been proposed for a possible commercial production. Sawdust was used as a feedstock for the simulation as it has above 29% of xylan content, which is a promising source for xylose recovery. The hydrolysis of hemicellulose and cellulose to its monomeric constituents and possible degradation of these monomers were modeled by a series of first-order reactions. A kinetic and stoichiometric based reactor was used for dilute acid hydrolysis and neutralization process. The main reactions involved were implemented for both reactor with specified kinetic parameter and conversion factor. The results from the simulation were compared with experimental study from literature. Results from the developed process model show a good agreement with experimental study with 2.4% overall mean error for xylose production and 4.5% overall mean error for glucose production.